Do nurses believe that the implementation of 'Caring around the Clock' is improving patient care? - Whittaker, Holly (2014)
Abstract Aim – The aim of this dissertation is to identify whether nurses believe that a new hourly rounding initiative is improving patient care by exploring how nurses define ‘care’, identifying how well the scheme is being used on wards and ascertaining nurse’s perceptions of the scheme. Background –The government has suggested that hospitals implement ‘hourly rounding’ initiatives to improve patient satisfaction and to reduce the number of incidents occurring in healthcare. Caring Around the Clock is a new hourly rounding scheme that has been implemented in an East Midlands NHS Trust, however the scheme is not being used as intended by nurses and this has prompted a service evaluation. Methods- Two wards volunteered to take part in this service evaluation and two qualitative approaches were undertaken in order to achieve the aims. Firstly, four hour and half observations were undertaken on two wards which took in to consideration issues such as staffing levels and whether the scheme was used. Secondly, ten semi-structured interviews were carried out with nurses from a range of job roles over the same two wards. Interviews focused on nurse perceptions of a ‘caring role’ and whether Caring Around the clock is helping them to fulfil their perceived caring role. Findings- The evaluation highlighted that nurses have a varied view of a caring role and that this can be linked to the amount of experience that a nurse has. Nurses are not using the scheme because it is not a driver for, there are not enough staff to implement it properly and because the majority of ward staff received limited training on the initiative. Conclusion- Nurses do not believe that Caring Around the Clock is improving patient care however it is also likely that underlying issues, such as staffing levels, are affecting the schemes success.